Faktor-Faktor yang Mempengaruhi Masyarakat Berwakaf Uang di Dompet Dhuafa - Imam, Nurul; Huda, Nurul (Badan Wakaf Indonesia, 2022)
This study aims to determine the effect of exogenous variables on endogenous variables in cash waqf so that this research can be a reference for money waqf institutions so that cash waqf can develop and benefit the benefit of the people. and make the data processed using spss, sem smart application pls. The variables in this study are Islamic religiosity, product knowledge, trust and consumer interest which have positive and significant results, so the solution of this research is that institutions or governments need to periodically educate and certify waqf nazhir so that Indonesians are interested in doing waqf because of the data from the people in Jakarta. Bogor Depok Tangerang, Bekasi, there are still many who do not understand about cash waqf.